Pequenos ruminantes e ozônio na superação da dormência de sementes florestais - Almeida, Robevania da Silva Alves (2023)
The Caatinga biome is home to thousands of flora species, which originated from a series of ecosystem processes. Species of the Fabaceae family that occur in this biome have ecological, social and energetic potential. However, most of its seeds have integumentary dormancy, which can prevent the resumption of germination, lack of uniformity and loss of production. Thus, we emphasize the importance of research that makes it possible to overcome dormancy in these species. Therefore, the objective of this study was to evaluate the passage of seeds through the digestive system of small ruminants, as well as the exposure of seeds to ozonated water, as methods of overcoming tegumentary dormancy. The work was divided into two stages, each one described in the form of a chapter. In chapter 01, the passage of Libidibia ferrea (ironwood) and Senna spectabilis (canafístula) seeds through the digestive system of goats and sheep for different periods was evaluated. Evaluating the number of recovered seeds, germination (%), germination speed index, average germination time, shoot and root length (mm) and shoot and root dry mass (g). The passage through the digestive system of goats and sheep is effective for overcoming dormancy of L. ferrea and S. spectabilis seeds, providing greater physiological performance (33 and 35% respectively) compared to intact seeds, that is, those that did not pass through the animals' intestines. In chapter 02, three concentrations of O3 (0, 10 and 20 mg.L-1) were evaluated for five conditioning periods (0, 30, 60, 90 and 120 min), in seven forest species. Subsequently, the first germination count (%), percentage of germination, germination speed index, digital length of seedlings (mm) and dry mass of seedlings (g) were evaluated. In general, O3 concentrations enable the germination of all the seeds studied, as well as, The concentration of 20 mg.L-1 of ozone is produced to express the vigor of the seeds, giving greater length to the seedlings. The methods for overcoming tegumentary numbness used in this study have great potential for use, emphasizing the importance of carrying out complementary studies that investigate different ways of adding seeds to the food base of small ruminants, as well as the analysis of hospitalizations and more intense periods of O3 such as vomiting to overcome tegumentary numbness.